Nursing students and depressive symptomatology: an observational study in University of Palermo. Issue 2 (29th November 2019) - Santangelo, Omar Enzo; Provenzano, Sandro; Giordano, Domiziana; Alagna, Enrico; Armetta, Francesco; Gliubizzi, Claudia; Terranova, Antonio; D'Anna, Giuseppe; Barresi, Dalila; Grigis, Dimple; Genovese, Cristina; Squeri, Raffaele; et al.
Abstract : Purpose: Depression is a common and serious medical illness, considered as a public health issue because it interferes with the interpersonal, social and professional functioning of the individual, and its frequency is constantly increasing. According to a recent review, approximately 34 per cent of nursing students had experienced depression worldwide. The university period may represent a moment in which the mental well-being of students is subjected to stress with a relative predisposition to the development of diseases related to mood disorders. The purpose of this study is to estimate the prevalence and examine the socio-demographic correlates of depressive symptomatology. Design/methodology/approach: In April 2019, a questionnaire was administered to all the nursing students of University of Palermo of the three years of course, accompanied by informed consent. Multivariable logistic regression was performed. The statistical significance level chosen for all analyses was 0.05. The results were analyzed using the STATA statistical software version 14. Results are expressed as adjusted odds ratio (aOR) with 95 per cent confidence intervals. Findings: The sample consists of 493 students who completed the questionnaire, and the average age of the sample participants is 21.88 years. The multivariable logistic regression model shows that the risk to have depressive symptomatology is significantly associated with the following independent variables: female gender (aOR 1.91), being single (aOR 1.87), second year of study (aOR 1.94), third year of study (aOR 1.92), not performing regular physical activity (aOR 1.78) and perceived low health status (aOR 3.08). Originality/value: This study shows that belonging to the female gender, being further along in the years of study, having a chronic illness and perceiving a low state of health are all factors that can increase the risk of developing the symptoms of depression; rather, regular physical activity, friendship and romantic relationships can be considered factors protecting them from the risk of falling into depression that can undermine both the study and work performance. Certainly, it is important to analyze all the involved variables to improve the global health not only of the nursing students but of all the students.